Tick control management practices of dairy farmers in Kangra district of Himachal Pradesh, India - Thakur, Devesh; Dinesh, Krishnender; Sharma, Manoj; Ravikumar, RK; Masand, Rupali; Sharma, Devina (Indian Journal of Dairy Science, 2022)
Tick infestation is a major problem affecting farm animal welfare and productivity. The study was conducted to assess the nature of tick infestation, awareness and methods of tick control among eight purposively selected village panchayats of district Kangra, Himachal Pradesh. Further out of these 8 panchayats, 200 dairy farmers were randomly selected during 2018-2019.The study indicated that tick infestation is acute in hilly regions of Himachal, India and farmers rely mainly on animal husbandry institutions for seeking scientific inputs/information. Synthetic acaricides were widely in practice (100.0%), though 40 percent of farmers relied on both synthetic and indigenous herbal medications. The high use of acaricides was due to the presence of veterinary institutions in every village panchayat in the region. The majority of dairy farmers (79.5%) reported that these synthetic acaricides were effective up to 30 days only and recurrent infestation on animals was noticed. Suitable extension interventions for improved housing management and proper tick disposal must be applied to overcome the problem in the region.